2x+4=3(x-4)
solve the equation below :-
2x+4=3(x-4)
x = 16
=> 2x+4 = 3(x-4)
=> 2x+4 = 3x-12
=> 2x+4 - 4 = 3x-12 - 4 (Subtract 4 on both the sides)
=> 2x = 3x-16
=> 2x-3x = -16
=> -x = -16
=> -x/-1 = -16/-1
=> x =16
Answer:
Step-by-step explanation:
Answer:
yes
Step-by-step explanation:
2) ( x + 3 ) ( x + 4 )
3) ( x + y ) ^2
4) ( 2x + 1 ) ( x - 3 )
→To simple the given equations
→
→
→
→
→
→
→
→
→
→
→
★What do you mean by simplifying an equation:
★Steps we can do to simplify the equation:
thankyou ❤️